Clinical outcomes for young people with screening-detected and clinically-diagnosed rheumatic heart disease in Fiji. (1st August 2017) - Engelman, Daniel; Mataika, Reapi L.; Ah. Kee, Maureen; Donath, Susan; Parks, Tom; Colquhoun, Samantha M.; Carapetis, Jonathan R.; Kado, Joseph H.; Steer, Andrew C.
Abstract: Background: Echocardiographic screening is under consideration as a disease control strategy for rheumatic heart disease (RHD). However, clinical outcomes of young people with screening-detected RHD are unknown. We aimed to describe the outcomes for a cohort with screening-detected RHD, in comparison to patients with clinically-diagnosed RHD. Methods: A retrospective cohort study included all young people with screening-detected RHD in the Central Division of Fiji in the primary cohort. Screen-negative and clinically-diagnosed comparison groups were matched 1:1 to the primary cohort. Data were collected on mortality, clinical complications and healthcare utilisation from the electronic and paper health records and existing databases. Results: Seventy participants were included in each group. Demographic characteristics of the groups were similar (median age 11 years, 69% female, median follow-up 7 years). There were nine (12.9%) RHD-related deaths in the clinically-diagnosed group and one (1.4%) in the screening-detected group (Incident Rate Ratio: 9.6, 95% CI 1.3–420.6). Complications of RHD were observed in 39 (55.7%) clinically-diagnosed cases, four (20%) screening-detected cases and one (1.4%) screen-negative case. There were significant differences in the cumulative complication curves of the groups ( p  < 0.001). Rates of admission and surgery were highest in the clinically-diagnosed group, and higher in the screening-detected than screen-negative group. Conclusions: Young people with screening-detected RHD have worse health outcomes than screen-negative cases in Fiji. The prognosis of clinically-diagnosed RHD remains poor, with very high mortality and complication rates. Further studies in other settings will inform RHD screening policy. Comprehensive control strategies are required for disease prevention.